MENINGKATKAN IMAN KAUM BAPAK-BAPAK MELALUI DOA ROSARIO DI KBG IV RATU DAMAI, STASI KUNJUNGAN ST PERAWAN MARIA PAMAKAYO - Krisantus Kenato; Alfonsius Mudi Aran (Adiba Aisha Amira, 2026)
This community service activity aimed to strengthen the faith and participation of fathers through the Rosary prayer in KBG IV Ratu Damai, Stasi Kunjungan Santa Perawan Maria Pamakayo. The activity was motivated by the low involvement of fathers in neighborhood prayer activities and the need to strengthen their role as spiritual leaders within the family. The method used was a community-based pastoral assistance approach through collective Rosary prayers, faith deepening sessions, experience sharing, and spiritual reflections conducted over four weeks. The participants consisted of 20 fathers. Data were collected through observation, interviews, and pre-test and post-test questionnaires using a Likert scale. The data were analyzed descriptively using quantitative and qualitative approaches. The results showed a significant increase in fathers’ participation, reaching 80% in neighborhood prayer activities and liturgical services. In addition, the activity strengthened spiritual awareness, enhanced family and community solidarity, and fostered the understanding that prayer is a source of strength for Christian family life. The participatory pastoral approach proved effective in encouraging active involvement and strengthening the faith life of fathers within both family and Church communities.